2011
DOI: 10.1007/s00455-011-9337-1
|View full text |Cite
|
Sign up to set email alerts
|

VFS Interjudge Reliability Using a Free and Directed Search

Abstract: Reports in the literature suggest that clinicians demonstrate poor reliability in rating videofluoroscopic swallow (VFS) variables. Contemporary perception theories suggest that the methods used in VFS reliability studies constrain subjects to make judgments in an abnormal way. The purpose of this study was to determine whether a directed search or a free search approach to rating swallow studies results in better interjudge reliability. Ten speech pathologists served as judges. Five clinical judges were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Additional studies are required to investigate the thoraco-abdominal biomechanics in the supine and LD postures. Third, pre-swallow jaw motion or tongue muscle activity affects the resting position of the hyoid bone and larynx [ 18 ]. Compared with the UP posture, the LD posture increases the difficulty in holding the food bolus still, which increases the effort of the tongue just before swallowing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies are required to investigate the thoraco-abdominal biomechanics in the supine and LD postures. Third, pre-swallow jaw motion or tongue muscle activity affects the resting position of the hyoid bone and larynx [ 18 ]. Compared with the UP posture, the LD posture increases the difficulty in holding the food bolus still, which increases the effort of the tongue just before swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of all data was conducted using SPSS version 14.0 (SPSS Inc., Chicago, IL, USA). Cohen’s d was calculated using R [ 18 ] and the package “effsize” [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Six measures used more items than the mean; none scored positive for reliability overall. Two of the six received conflicting ratings (26,56) and two negative (57,58), one scored 'indeterminate' (41), and one study was not evaluated due to 'poor methodological quality' (59). It should also be noted that two studies reported reliability for two different protocols (green coloured boluses vs. white) and diagnoses (aspiration or dysphagia) (43,44); both scored positive for reliability overall in only one protocol or diagnosis (green bolus and dysphagia respectively).…”
Section: Included Measuresmentioning
confidence: 99%
“…[61][62][63] Reliability improves when raters routinely use scales such as the MBSImps or the penetration/aspiration scale. Both assessments are difficult to conduct with patients who have attention and behavioural difficulties and where there are likely to be movement artefacts.…”
Section: Instrumental Assessmentsmentioning
confidence: 99%